Foot Screening dan Pengaruh Edukasi terhadap Pengetahuan dan Perilaku Pencegahan Diabetic Foot Ulcer pada Individu dengan Diabetes Mellitus - Nazier, Suci Anatasia; Karma, Agusni (Jurnal Kesehatan, 2021)
Diabetic foot ulcer (DFU) is a complication of diabetes mellitus (DM) that is important to get attention especially by people with DM. Approximately 25% of DM cases develop DFU. In addition, 85% of amputations in DM cases are caused by DFU. However, amputation of the lower limb due to DFU could be minimized by giving education about its prevention. Therefore, this study was conducted to determine the risk level of DFU and evaluated the effect of education related to DFU prevention in people with DM. This research was an observational descriptive study with a cohort study approach. This research had 15 participants. Each participant underwent foot screening to determine the risk level of DFU. Afterward, they were given a pretest to evaluate the level of knowledge and behavior of DFU prevention by using questionnaires. Directly after the pretest, they were also given education about DFU prevention. After 6-8 weeks, a post-test was carried out using the same questionnaires. The results showed that all participants had a risk of developing DFU. Giving education has significantly improved the knowledge and behavior of participants in practicing foot care to prevent DFU. It is important to perform foot screening to prevent the complications of DFU. In addition, education is significantly influential in improving the knowledge and behavior related to DFU prevention in people with DM.